Age-related immunosenescence and Epstein–Barr virus-positive mucocutaneous ulcer presenting as oral cancer: a case report - Jiayuan Ye; Shengqiang Ji; Zhouxiao Wu; Genhua Ma; Jing Chen; Shimin Wu; Yilian Xie (Frontiers in Medicine)
Epstein–Barr virus-positive mucocutaneous ulcer (EBVMCU) is a rare condition characterized by skin or mucosal lesions resulting from defective immune surveillance of EBV due to immunosuppression, which can be iatrogenic or age-related. It represents a benign lymphoproliferative disorder that clinically may mimic malignant tumors. However, EBVMCU typically progresses slowly and often resolves spontaneously without specific treatment, emphasizing the critical need for differential diagnosis from malignancies. In this study, we report a case of EBVMCU in an elderly patient demonstrating ulcers on the oral mucosa, buccal area, and maxillary mucosa, with associated bone destruction, which was initially suspected to be an oral malignancy but was confirmed as EBVMCU through biopsy. This case underscores the importance of considering EBVMCU in elderly patients with unexplained persistent mucosal ulcers to exclude malignancies. In addition, attention should be given to unhealthy lifestyle habits such as smoking and drinking, as well as poor oral hygiene, which are potential factors that increase the risk of this disease and contribute to worse prognoses.